Some Legal Aspects of Abbreviated Trial in Albania - Mëçalla, Naim; Jurgen Mëçalla (European Journal of Multidisciplinary Studies, 2017)
The Criminal Procedure Code of the Republic of Albania, as amended, came as an expression of the society’s need for a more effective fight against criminality, a process that should go hand in hand with respect of the human rights and fundamental freedoms. This code, among other things, brought a new concept with regard to the possibility of applying special proceedings, as alternatives to the ordinary proceedings of investigation and judgment in the criminal cases. Thus, after nearly half a century, is reinstated in the Criminal Procedure Code, the special proceedings institute and for the first time in the history of the Albanian procedural law, an abbreviated trial, is foreseen as an alternative judgment. In this context, this paper gives an overview of the abbreviated trial, its legal meaning and the advantages it brings to the parties in particular and to the criminal process in general. The paper also contains a synthesized review of the abbreviated trial, under Albanian legislation and addresses some of the issues of judicial practice, as well as a brief presentation at a practical point of view of the abbreviated trialcases, answering some of the problems arising from the practice.